Psychometric Properties and Measurement Invariance of the 3×2 Achievement Goals Questionnaire for Exercise (3×2 AGQ-E) among Chinese Mainland adolescents - Xiaofei Lin; Shamsulariffin Samsudin; Soh Kim Geok; Nasnoor Juzaily Mohd Nasiruddin; Lixia Bao; Junlong Zhang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study aimed to evaluate the psychometric characteristics of the 3×2 Achievement Goals Questionnaire for Exercise (3×2 AGQ-E) tailored for Chinese mainland adolescents in an exercise context. Participants included adolescents from junior and senior high schools across mainland China. study investigation focused on factorial validity, discriminant validity, internal consistency reliability, and measurement invariance across gender and academic levels of the 3×2 AGQ-E. Confirmatory factor analysis upheld the proposed multi-dimensional structure (CFI = .0.992, TLI = 0.972, RMSEA = 0.042). Inter-factor correlations, examined within a 95% confidence interval, underscored the discriminant validity of the 3×2 AGQ-E, indicating its capability to assess interconnected yet distinct constructs. The instrument demonstrated excellent internal consistency (Cronbach's α>0.80). The nomological validity was supported by a consistent pattern in inter-factor correlations. Multi-group confirmatory factor analysis suggested robust measurement invariance, with consistent factor loadings and variances-covariances across genders (△=0.000 to 0.007) and academic levels (△= 0.001 to 0.014). This research provides crucial psychometric support for the 3×2 AGQ-E, enhancing its utility for future research and application in understanding achievement motivations among Chinese mainland adolescents in the context of exercise and physical activities.